Effect of Pre-exposure Use of Amantadine on COVID-19 Infection: A Hospital-Based Cohort Study in Patients With Parkinson's Disease or Multiple Sclerosis - Kamel, Walaa A.; Kamel, Mohmed I.; Alhasawi, Almunther; Elmasry, Sameh; AlHamdan, Fajer; Al-Hashel, Jasem Y. (Frontiers in Neurology, 2021)
Background: Amantadine has been proposed to be able to inhibit E- channel conductance in reconstituted lipid bilayers of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We aimed to study whether patients on amantadine have altered risks of contracting COVID-19 infection. Methods We did a prespecified observational, hospital -based retrospective cohort study using hospital data for patients on amantadine supported by data given by the patients through an online questionnaire. We included registered amantadine users in our hospital for 6 months or more on March 1, 2020 along with diagnosis matched control group of non- amantadine users. We used forced entry multiple logistic regression models to estimate adjusted ORs for amantadine adjusting for the confounders. Findings Between September 1, 2019, and March 1, 2020, 212 patients with Parkinson’s disease (PD) or multiple sclerosis (MS) received two or more prescriptions of amantadine. Between March 1,2020 and March 1, 2021, findings Of 256 compliant patients who had responded to our on line questionnaire ,87 patients were on amantadine (group I) ,169 patients were not on amantadine (control group, group II), COVID-19 disease infection was confirmed in 5.7%, 11.8% in group I, II patients respectively. Older age, comorbidity burden, and history of contact with COVID cases were each associated with increased odds of COVID-19 in multivariable-adjusted models. Amantadine was associated with a significantly reduced risk of COVID-19 disease infection (adjusted OR 0.256 ,95% CI 0.074 to 0.888. Interpretation: Amantadine is associated with reduced risk of COVID-19 infection after adjusting for a wide range of variables. Comorbidities and old age are considered as risk factors for COVID-19 infection. Therefore, completion of randomized trials investigating pre-exposure prophylactic use of amantadine for prevention of COVID-19 are warranted